Examining factors that effect on the acceptance of mobile commerce in Malaysia based on revised UTAUT - Mohammed A. Sabri Alrawi; Ganthan Narayana Samy; Rasimah Che Mohd Yusoff; Bharanidharan Shanmugam; Rajasekaran Lakshmiganthan; Nurazean Maarop; Norshaliza Kamaruddin (Institute of Advanced Engineering and Science, 2020)
This study presents an amended unified theory of acceptance and use of technology (UTAUT) which explores key factors affecting Malaysian consumers ' willingness to accept mobile-commerce. A questionnaire survey has been used to collect information from 400 Malaysian smartphone users using a random stratified sample and analyzed using structural equation modelling (SEM); with the use of Smart PLS 3.0. Results show that acceptance and use of mobile-commerce services can also be predicted by the behavioural intentions of users, whose performance expectancy, efforts expectations, social effects, mobility, personal innovations and perceived trust are significantly affected. From these variables, perceived trust is the most significant determinant that directly affects behavioural intention to use mobile-commerce services in Malaysia. It is then followed by mobility, personal innovation, social influence, performance expectancy then effect expectancy. Facilitating Conditions and moderating variables such as gender, age, education, income, marital status, experience and payment have no significant effect on Behavioral Intention to use mobile-commerce services in Malaysia. In conclusion, this study shows that behavioural intention and the use of mobile commerce services in Malaysia have a direct effect. The study will help dealers to avoid spending thousands of dollars on investments that have little impact on whether the customer is embracing and using mobile-commerce. The study also provides quantified indicators and offers a framework for the understanding of the Malaysia mobile-commerce system. The report concludes with a study of the effects of the research findings and provides recommendations for future research.